THE INFLUENCE OF ACTIVENESS IN JOINING EXTRACURRICULAR ACTIVITY ON STUDENTS’ SOCIAL INTELLIGENCE - Fuadah, Wina Nurul (International Journal Pedagogy of Social Studies, 2018)
This research is conducted based on the observation in SMP Negeri  3 Jatinangor that many students do not join  in any extracurricular activity and have the low social intelligence. This research aims to know the influence of the activeness in joining extracurricular activity on students’ social intelligence. The method of the research is correlational method with analyzing technique using Rank Spearman correlation. The subjects of the research were 137 students at Class IX SMP Negeri 3 Jatinangor. The instrument used in this research was questionnaire to measure the activeness in joining extracurricular and students’ social intelligence. The data were analyzed by using t-test assisted by SPSS 22.00 for windows. The result of the research shows that there is positive and significant influence when the students are involving actively in extracurricular activity at class IX SMP Negeri 3 Jatinangor with the high correlation level. This means that being active in joining extracurricular activity can be one of the significant factors to influence the students’ social intelligence.Key words : Extracurricular, The activeness, Social Intelligence, Correlational meth